Analisis Penerapan Model Picture and Picture Terhadap Keterampilan Menulis Karangan Deskripsi di Sekolah Dasar - Azzahra, Hapsah; Endah Sugiharti , Rini; Rasis Najwan, Mohammad (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
This article explores the challenges faced by elementary school students in writing descriptive essays. Previous research has identified several issues, including difficulties in understanding the topic, selecting appropriate opening words due to their abstract nature, linking sentences cohesively, adhering to the no guidelines of PUEBI (the Indonesian standard for writing), effectively conveying ideas, and a monotonous learning experience that lacks engaging instructional models. An analysis of various studies suggests that the "picture and picture" teaching model is the most effective method for enhancing students' descriptive writing skills. The objective of this study is to assess the impact of this model on improving the ability to write descriptive essays. Employing Systematic Literature Review methodology, the research follows a PICO framework, analyzing 15 journals published between 2014 and 2024. The review considers the year of publication, research methods employed, and the grade levels examined.The findings confirm that the "picture and picture" model significantly enhances elementary students' skills in writing descriptive essays.